Literature Review: Masalah Psikologis pada Ibu Hamil selama Masa Pandemi Covid-19 - Arum Meiranny; Alivia Nurrokhmah; Jihan Diya Yumna; Siti Zulaekhah (Universitas Faletehan, 2022)
The number of COVID-19 infection cases was increased day by day worldwide. In 2021, World Health Organization recorded that the cases reached 209,876.613 people. One of the people who were at high risk of being exposed to COVID-19 quickly were pregnant women. The purpose of this study was to determine the psychological problems of pregnant women during COVID-19 period by using a literature review research method. Searches were made on Google Scholar, NCBI, Elsevier and PubMed by using the keywords psychological problems, pregnant women, and COVID-19 and the search criteria in the year of publication 2020. The data search was carried out in English and Indonesian. Of all the articles, 6 articles met the desired criteria. Based on the literature study that had been done, the researchers concluded that the psychological problems of pregnant women during COVID-19 pandemic were increased anxiety and depression.